Timings for HbA1c testing in people with diabetes are associated with incentive payments: an analysis of UK primary care data. Issue 1 (21st September 2018) - Hirst, J. A.; Farmer, A. J.; Smith, M. C.; Stevens, R. J.
Abstract: Aims: Guidelines recommend testing HbA1c every 3–6 months in people with diabetes. In the United Kingdom (UK), primary care clinics are financially incentivized to monitor HbA1c at least annually and report proportions of patients meeting targets on 31 March. We explored the hypothesis that this reporting deadline may be associated with over‐frequent or delayed HbA1c testing. Methods: This analysis used HbA1c results from 100 000 people with diabetes during 2005–2014 in the Clinical Practice Research Datalink UK primary care database. Logistic regression was used to explore whether the four months prior to the deadline for quality reporting (December to March) or individual's previous HbA1c were aligned with retesting HbA1c within 60 days or > 1 year from the previous test, and identify other factors associated with the timing of HbA1c testing. Results: Retesting HbA1c within 60 days or > 1 year was more common in December to March compared with other months of the year (odds ratio 1.06, 95% confidence interval 1.04–1.08 for retesting within 60 days). Those with higher HbA1c were more likely to have a repeat test within 60 days and less likely to have a repeat test > 1 year from the previous test. Conclusions: We have found that retesting HbA1c within 60 days and > 1 year from the previous test was more common in December to March compared with the other months of the year. This work suggests that both practice‐centred administrative factors and patient‐centred considerations may be influencing diabetes care in the UK. What's new?: This is the largest analysis to explore factors associated with timings of HbA1c tests in people with diabetes in the UK. Timings of repeat HbA1c tests are associated with the Quality and Outcomes Framework reporting deadline and participants' previous HbA1c . People with higher HbA1c were more likely to be retested within 60 days compared with those with well‐controlled diabetes. Financial incentives appear to result in more over‐frequent or catch‐up HbA1c testing in the months approaching the reporting deadline than other months of the year in attempts to meet targets. This could have implications for future target‐based incentive programmes.